The analysis of cognitive restructuring techniques effectiveness to reduce the online game addiction - Rahmatillah, Nuzuli; Setiawati, Farida Agus (Universitas Negeri Padang, 2020)
In schools there are still many students who experience academic disorders such as lazy learning, often neglecting assignments, often skipping school, this is because one of them is because students are addicted to playing online games. This study aims to analyze the effectiveness of cognitive behavioral therapy (CBT) counseling with cognitive restructuring techniques to reduce online game addiction behavior of students. This research is a quantitative study with a quasi-experimental method. The population in this study were students who were addicted to online games. Sampling using a purposive sampling technique, so that the subjects in the experimental group were 8 students and the control group was 8 students. Data collection was done using online game addiction scale that has been tested for validity and reliability. Data analysis using score gain testing. The results showed that CBT cognitive restructuring techniques were effective in reducing online game addiction on students. The CBT cognitive restructuring techniques are effective in reducing online game addiction on students.